Crocs! - Greenberg, David (David T.) (Little, Brown, 2008)
Having moved from the city to a tropical island to escape such horrifying creatures as bugs and cats, a homeowner encounters a horde of friendly crocodiles, who drink Tabasco sauce, get tangled in dental floss, and turn the house into a swamp.